Pengaruh Gaya Hidup, Citra Merek, dan Kualitas Produk terhadap Minat Beli Smartphone Iphone - Hidayah, Munirotul Aina Bin Nur; Soebiantoro, Ugy; Zawawi, Zawawi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Competition in the industrial world that is increasingly developing makes companies vying to optimally increase their resources. As well as social changes in Indonesian society towards perusahaan berjuang untuk meningkatkan kualitas sumber daya mereka sementara dunia teknologi dan informasi maju dengan sangat cepat. Bisnis dapat menggunakan segmentasi pasar sebagai salah satu teknik pemasarannya. Dengan penelitian ini, it analyzes related to iPhone smartphone products, which are well-known brands throughout the world so that they are familiar to consumers' minds, but the market share of these brands has decreased. This research was conducted to examine evaluated the external and internal models with Smart PLS 4.0 software to determine the impact of lifestyle, brand image, and product quality on iPhone purchase intentions through the use of Partial Least Square (PLS) Structural Equation Modeling (SEM). The method used to collect data is known as proportional stratified random sampling. Respondents were 90 samples of economics and business faculties who know iPhone products. These results indicate that lifestyle, brand image, and product quality can influence the intention to buy an iPhone smartphone Keywords: Lifestyle, BrandImage, QualityProduct, PurchaseIntention